The designation and display of British railway heritage in the post-war decades - Lambert, Mark (2017)
This PhD thesis details the ways in which objects which were deemed to represent Britain’s railway heritage were designated as important and subsequently displayed or stored by the state-owned British Railways, and its’ Parent organisation (until 1962) the British Transport Commission, in the post-war decades. I focus particularly on the period between nationalisation in 1948 and the opening of the National Railway Museum in 1975, when responsibility for the preservation of historic railway objects passed to the Department of Education and Science (with the exception of paper records, which became the responsibility of the Public Records Office from 1972). In this period, the British Transport Historical Records Office was established in West London (with branches and York and Edinburgh), whilst a series of temporary exhibitions of railway history at the Shareholder’s Meeting Room in Euston in the 1950s were followed by the establishment of new transport museums at Clapham, South London in 1961 and at Swindon in 1962. Attempts by the British Transport Commission to preserve and display aspects of Britain’s railway history - and particularly, from 1951, those of its Curator of Historic Relics John Scholes and its Archivist Leonard Johnson- intersected with the increasing enthusiasm for railways amongst the general population, exemplified by the advent of new societies catering for this interest in addition to those established prior to the war, and also for the growing popularity of transport history as a subject of scholarly interest. This in turn took place in the context of increasing technological change on the network, notably the closure of thousands of miles of railway lines (often rural branch lines) and the abolition of steam locomotives in favour of diesel or electric power. This thesis shows that railway enthusiasts, through the Consultative Panel for the Preservation of British Transport Relics from 1958 onwards, played an active role in advising the Transport Commission on the preservation of railway heritage, notably the selection of historic locomotives to be saved for posterity. This thesis considers in detail the work of the Joint Locomotive Preservation Committee in 1948-1949 and of the Consultative Panel for the Preservation of British Transport Relics between 1958 and 1968, and also the interrelated activities and museum displays of the Curator and Archivist of Historic Relics at the British Transport Commission (later the British Railways Board) between 1951 and 1974 (1972 in the case of the Archivist), including the museum displays at the Railway Museum in York, the Great Western Railway Museum at Swindon and the Museum of British Transport at Clapham.